Peningkatan Aktivitas Enzim Metabolisme Sukrosa dan Glikolisis pada Tanaman Padi Transgenik Overekspresi Gen SoSPS1 - Ferdi Hariyanto; Bambang Sugiharto; Netty Ermawati; Wahyu Indra Duwi Fanata (Vegetalika, 2026)
Sucrose Phosphate Synthase (SPS) is a key enzyme in the sucrose biosynthesis pathway and plays an essential role in regulating sucrose accumulation in plants. Overexpression of the SPS gene has been reported to enhance sucrose accumulation and growth in various plant species. However, its effects on the dynamics of sucrose-metabolising and glycolytic enzymes in rice remain insufficiently explored. This study aimed to analyze the activities of sucrose metabolism enzymes, including SPS, invertases (acid and neutral), sucrose synthase (SuSy), and the glycolytic enzyme hexokinase (HXK) in transgenic rice plants overexpressing the SoSPS1 gene. The experiment was conducted using a completely randomized design with five genotypes, one of which was the wild type, and four transgenic rice lines, T4, T6, T8, and T9, with four replicates. The results showed that overexpression of the SoSPS1 gene led to significant increases in plant height and biomass, as well as markedly enhanced SPS activity in all transgenic rice plants compared to the wild type. Invertase activity (A-INV and N-INV) did not differ significantly among genotypes. In contrast, SuSy activity increased dramatically in transgenic lines T6, T8, and T9, suggesting that sucrose degradation in response to the genetic modification is primarily regulated through SuSy. The increase in SuSy activity was accompanied by the rise in HXK activity in the same lines (T6, T8, and T9). These results indicate that HXK subsequently phosphorylate hexose sugars, which may act as substrates for cellulose synthesis and activate the transcription factors that lead to higher biomass production. Overall, this study demonstrates that overexpression of SoSPS1 influences carbon flux and sugar metabolism, providing deeper insights into the relationship among sucrose biosynthesis, sugar sensing, and biomass enhancement in transgenic rice.